Water, State and the City - Ioris, A. author. aut Link
XII, 151 p.
Keywords: The book investigates the complexity of the Latin American mega cities and the multiple commitments of the apparatus of the state with a focus on the failures of the public water sector. It offers an innovative interpretation of large-scale urbanization, one of the most challenging questions affecting Latin American governments and society.